Unveiling the Motives of Ethical Behavior in Accounting Through Detective Conan Anime: an Interpretive Study of Behavior - Pinandita, Candra Pramula; Sugiartono, Endro; Andari, Atik Tri (Worksheet : Jurnal Akuntansi, 2025)
This research aims to explore the meaning of ethics and behavioral motives in the context of accounting through a narrative hermeneutic approach, drawing on the anime Detective Conan. Behavioral accounting views that accounting decision-making is not value-free but rather influenced by moral dilemmas, social pressures, and individual rationalization. This research analyzes several episodes of Detective Conan that feature inner conflicts, information manipulation, and dilemmas between honesty and loyalty. The analysis focuses on the narrative and dialogue of characters that represent the motives behind deviant actions, which are then interpreted using the Theory of Planned Behavior, Cognitive Moral Development, and Rest’s Four-Component Model. The findings suggest that the motivations behind actions in the anime have significant relevance to the ethical dilemmas faced by accountants, including instances of fraud, manipulative reporting, and the reluctance to disclose information. The narrative of anime presents the meaning of ethics as a social process that is not absolute but rather the result of negotiation between personal values and external pressures. These findings reinforce the position of popular culture as an alternative medium in accounting ethics education. Anime like Detective Conan can serve as a reflective and contextual medium that bridges theoretical understanding with the complex moral realities in the professional world.